The normal and pathological language (Conclusion) - Espejo, Luis D. (1920)
The ontogenetic evolution of language is an abbreviated recapitulation of the successive stages through which the language has atravezado by humans. And musical language mimics its appearance preceded the verbal language. The centers which govern the operation of the three forms of language, mimics, musical and verbal are independent.